Hydrogeochemistry in the Yukon-Tanana upland region of east-central Alaska: Possible exploration tool for porphyry-style deposits. (January 2021) - Kelley, Karen D.; Graham, Garth E.
Abstract: A hydrogeochemical study using high resolution ICP-MS was undertaken at the Taurus and other porphyry Cu–Mo(-Au) occurrences and Ag–Au–Cu (+/− Pb, Zn) occurrences with epithermal-style characteristics in the Yukon-Tanana upland region of eastern Alaska. Surface water samples were collected from 30 sites on creeks that drain known deposits and occurrences and surrounding presumably unmineralized areas. Water samples for the entire 9 km length of McCord Creek, which drains the Taurus deposit, and those from streams draining the areas at and near the Bluff and Dennison porphyry occurrences have high conductivity values (492–1250 μS/cm) and consistently high concentrations of B (3–250 μg/L), Co (2.3–42 μg/L), Mn (339–4750 μg/L), Re (0.012–0.1 μg/L), and SO4 2− (>200 mg/L), all of which are well above the median value for this data set and significantly greater than concentrations in water samples from the unmineralized areas. These are the best pathfinder elements specifically for porphyry style deposits because most of them are not anomalous in waters near epithermal occurrences. Copper concentrations are high (up to 115 μg/L) in some low-pH water samples from McCord Creek and drainages around Bluff, and a few near neutral pH waters have high molybdenum (>1 μg/L), but neither element is consistently anomalous in close vicinity to the porphyry occurrences, possibly due to a metal-poor, sulfide-poor leached cap (average of 50 m) that overlies supergene and hypogene mineralized zones and is the dominant rock at surface. High concentrations of Bi and/or As occur in many waters associated with mineralized areas, particularly the Bluff and Dennison occurrences. In general, the element associations related to porphyry deposits reflect the deposit mineralogy, as well as size of the footprint related to alteration and mineralization. Highlights: HR-ICP-MS analyses of stream waters identify porphyry occurrences in eastern Alaska. Specific conductance and elevated B, Co, Mn, Re, and SO4 2− are primary indicators. Concentrations of F, Cl, Tl, W, and REE are also effective pathfinders. Water chemistry distinguishes porphyry vs. epithermal occurrences. Variations in As and Bi concentrations suggest multiple mineralizing events.